Phosphate composite flame retardant and preparation method thereof

By using phosphorus-nitrogen graft-coated network-shaped silica powder, Co-MOF composite graphene oxide catalytic support and pentaerythritol phosphate in epoxy resin, the phosphate composite flame retardant is prepared, which solves the problem of insufficient flame retardant performance and thermal stability in the prior art, and achieves more efficient flame retardant effect and better thermal stability.

CN119708639AActive Publication Date: 2025-03-28SHANGHAI SIKAI TESTING TECH CO LTD

Patent Information

Application Number
CN202510061707.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-28
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing composite flame retardant system has poor compatibility with epoxy resin, resulting in poor flame retardant performance and insufficient thermal stability, which limits its application in resin matrix.

Method used

The phosphate composite flame retardant is prepared by melt blending technology to enhance flame retardant performance and thermal stability.

Benefits of technology

It significantly improves the flame retardant performance and thermal stability, forms a dense and continuous carbon layer, effectively isolate oxygen and heat, reduces smoke generation, and significantly improves the flame retardant performance of the epoxy resin matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708639A_ABST
    Figure CN119708639A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphate composite flame retardant and a preparation method thereof, and relates to the technical field of flame retardants. The phosphate ester composite flame retardant is prepared from phosphorus-nitrogen grafted and coated network-shaped silicon dioxide powder, a Co-MOF composite graphene oxide catalytic carrier and pentaerythritol phosphate ester, the phosphorus-nitrogen grafted coated network-shaped silicon dioxide powder is prepared from a network-shaped dispersion modifier, silicon dioxide, dopamine hydrochloride, phosphorus oxychloride and 4, 4-diaminodiphenyl methane, a Co-MOF composite graphene oxide catalytic carrier is filled with phosphorus-nitrogen grafted and coated network-shaped silicon dioxide powder and pentaerythritol phosphate, migration of components is effectively reduced, the thermal stability of a flame-retardant system is enhanced, meanwhile, the compatibility and dispersity in an epoxy resin matrix are improved, the phosphorus-nitrogen grafted and coated network-shaped silicon dioxide powder, the pentaerythritol phosphate and the phosphorus-nitrogen grafted and coated network-shaped silicon dioxide powder have a synergistic effect, and the flame-retardant effect is improved. A carbon residue layer after combustion is more compact and continuous, isolation and protection effects can be better played, and the flame retardant property is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardants, and specifically refers to a phosphate composite flame retardant and a preparation method thereof. Background Art

[0002] Epoxy resin has become one of the important matrix materials for coatings, electronic materials and fiber-reinforced composites due to its excellent mechanical properties, high adhesion strength, good heat resistance and high electrical resistivity. However, epoxy resin is flammable when exposed to open flames, and the combustion process releases a large amount of toxic gases, which seriously endangers human life and health. Halogen-based flame retardants will release toxic smoke and gases during the epoxy resin flame retardant process, posing a huge threat to the environment. Therefore, halogen-free flame retardants are gradually replacing halogen-containing flame retardants and becoming a new trend in the emergence of epoxy resin flame retardants.

[0003] Adding phosphorus flame retardants has become one of the main ways to improve the flame retardant properties of epoxy resins. The advantages of this flame retardant are significant flame retardant effects, less smoke emissions, and less impact on the ecological environment. Phosphorus flame retardants can also be used in the lubricant industry. They can effectively enhance the fire resistance of lubricants, especially in harsh environments such as high temperature, high pressure, flammable and explosive. The use of lubricants containing flame retardants can ensure the safe operation of equipment and reduce the risk of fire. Compared with traditional halogen flame retardants, phosphorus flame retardants have broader application prospects. They can play a flame retardant role in both gas phase and solid phase. In the gas phase process, phosphorus compounds produce PO· to ​​quench free radicals such as H· and HO·, reducing the concentration of combustible gases produced during combustion to terminate the combustion chain reaction. In the condensed phase, phosphorus-containing compounds begin to decompose at a lower temperature to produce substances such as phosphoric acid and polyphosphoric acid. The generated phosphoric acid substances cover the surface of the material, which can not only prevent the release of combustible gases, but also have dual barrier functions of heat insulation and oxygen isolation.

[0004] The existing technology currently has the following problems:

[0005] The commonly used compound flame retardant system has poor compatibility with matrices such as epoxy resin, which is not conducive to uniform dispersion in the resin matrix. In addition, the thermal stability of the organic components in the flame retardant system is general and they are easy to migrate in the resin matrix, which greatly limits the flame retardant performance. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a phosphate composite flame retardant, comprising the following components in parts by weight: 30-40 parts of phosphorus-nitrogen grafted coated network silica powder, 10-20 parts of Co-MOF composite graphene oxide catalytic carrier, and 10-20 parts of pentaerythritol phosphate.

[0007] The phosphorus-nitrogen grafted coated network silicon dioxide powder comprises the following components in parts by weight: 20-25 parts of a network dispersion modifier, 60-75 parts of silicon dioxide, 10-15 parts of dopamine hydrochloride, 3-6 parts of phosphorus oxychloride, and 6-8 parts of 4,4-diaminodiphenylmethane.

[0008] The Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 30-40 parts of Co-MOF and 10-15 parts of graphene oxide.

[0009] The method for preparing the phosphorus-nitrogen grafted coated network-like silica powder specifically comprises the following steps:

[0010] (1) 1 mol of KH550 and 1 mol of KH560 were added to a three-necked flask in a nitrogen atmosphere, heated to 120-130°C under magnetic stirring, stirred for 3-5 hours, and cooled to room temperature. The primary amine group of KH550 and the epoxy group of KH560 underwent an epoxy ring-opening reaction to synthesize a network-like substance with three alkoxy groups at both ends, thereby obtaining a network-like dispersing modifier;

[0011] (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, and then use hydrochloric acid solution to adjust the pH to 4.0, then add the network dispersing modifier described in step (1), stir at 40-50° C. for 4-5 hours, add 6.0-7.5 g of silica powder to the modified solution. At high temperature, silica can form a dense barrier layer on the surface of the material to isolate oxygen and heat and prevent the spread of combustion. Heat to 60° C., stir and mix thoroughly for 4-5 hours, stir at a speed of 500-600 rpm, dry, and crush. The alkoxy groups at both ends of the network dispersing modifier are simultaneously grafted onto different silica particles, connecting a large number of silica particles to form a network silica structure with a larger overall particle size. At the same time, there are certain gaps between the silica particles, which reduces the adsorption and aggregation between the particles and effectively increases the exchange interface of the flame retardant system, thereby improving the flame retardant properties of silica to obtain network silica;

[0012] (3) Weigh 0.6-1.0 g of the networked silica described in step (2) and add it to 100 mL of Tris-HCl buffer and ultrasonically treat it for 10-20 min. Then add dopamine hydrochloride to 200 mL of Tris-HCl buffer and dissolve it completely. Then pour the networked silica dispersion into it and ultrasonically treat it for 10-15 min. Place it in a 25°C water bath and stir it magnetically at a speed of 160-180 rpm for 6-12 h. Then centrifuge it twice at a speed of 7000-8000 rpm. The first centrifuge The time is 15 minutes, the second centrifugation time is 10 minutes, the precipitate is freeze-dried and ground, and polydopamine wraps the silica particles with a layer of "nano-coat" rich in catechol groups, which has excellent adhesion and film-forming properties and can be used for further modification and functionalization. It can improve its compatibility and dispersibility in the epoxy resin matrix and significantly improve thermal stability. In addition, the polydopamine coating forms a protective layer during the combustion process, which can isolate oxygen and heat, thereby interrupting the combustion process and reducing the generation of smoke. Polydopamine@network silica is obtained;

[0013] (4) Weigh 0.5-1.0 g of the polydopamine@network-shaped silica described in step (3), 0.3-0.6 g of phosphorus oxychloride liquid, 50 mL of THF and 0.3 g of triethylamine liquid, add them into a 250 mL three-necked flask in sequence, and ultrasonicate at 25°C for 0.5-1 h. Then, dissolve 0.6-0.8 g of 4,4-diaminodiphenylmethane solid in 20 mL of THF and slowly drip it into the three-necked flask within 1 h. Let it react at room temperature for 24 h. The product is washed with THF and deionized water in sequence and dried. By introducing phosphorus and nitrogen elements on the surface of polydopamine@network-like silica by grafting, the thermal stability and flame retardancy of the composite are improved. Polydopamine@network-like silica effectively adheres to the surface of the matrix such as epoxy resin, isolating the external combustible gas and heat from entering the matrix. The phosphorus and nitrogen small molecules will be degraded first when heated, effectively promoting the dehydration of the epoxy resin matrix into carbon, and synergistically acting with the protective layer formed when the silica particles burn to block the release of heat and smoke, thus obtaining phosphorus-nitrogen grafted and coated network-like silica powder;

[0014] Preferably, in step (2), the amount of the network dispersing modifier added is 2.0-2.5 g, and the alkoxy groups at both ends can react with the active hydroxyl groups on the surface of silica to achieve graft modification of silica;

[0015] Preferably, in step (3), the amount of dopamine hydrochloride added is 1.0-1.5 g, and dopamine hydrochloride self-polymerizes to form a polydopamine protective layer, the outer layer of which is arranged with evenly distributed hydroxyl groups.

[0016] The present invention also provides a method for preparing a phosphate composite flame retardant, which specifically comprises the following steps:

[0017] S1. Add 70 mL of 98% concentrated sulfuric acid to a 1000 mL beaker under an ice bath, stir and add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 0-4 ° C, stir thoroughly, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 10-30 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after 15 min of reaction, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry. Graphene oxide can be used as a flame retardant additive. Its unique two-dimensional sheet structure can promote the material to form a dense and continuous carbon layer during the combustion process, isolate heat transfer and gas exchange with the outside world, and obtain graphene oxide;

[0018] S2. Add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water, stir for 0.5-1 h, and then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 160-170 ° C, and the reaction time is 48-72 h. A new cobalt-based MOF material is synthesized by a hydrothermal method using a mixed ligand of cobalt salt and Fbtx and H2dcpa. The material has good thermal stability and adsorption, can maintain structural stability at high temperatures, and adsorb harmful gases and smoke produced by combustion, reducing the release of toxic gases in fires. The transition metal cobalt has catalytic properties, which can promote carbonization reaction during combustion to form a more stable carbon layer, thereby isolating oxygen and heat, slowing down the combustion rate, and obtaining Co-MOF.

[0019] S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 100-200mL methanol solution, ultrasonically dispersing for 30-50min, stirring for 1-2h, standing for precipitation, filtering and washing, and drying. The Co-MOF is evenly distributed on the surface of the graphene oxide and tightly combined. The carbon layer generated by the combustion of the formed composite carrier is dense and maintains a certain geometric shape, is not easy to fall off, and the coverage of the carbon layer is denser and wider. At the same time, in the composite carrier, the graphene oxide can also promote the rapid carbonization of the polymer and produce a variety of non-combustible gases when thermally decomposed. These gases can isolate oxygen from contact with combustible gases and block the continuous combustion conditions, thereby playing a flame retardant role, and obtaining a Co-MOF composite graphene oxide catalytic carrier;

[0020] S4, the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3 and pentaerythritol phosphate are uniformly mixed, the molecular structure of pentaerythritol phosphate presents a highly symmetrical cage shape, has excellent thermal stability and carbon-forming property, and provides abundant acid source and carbon source at the same time, and the mixture is melt-blended in an internal mixer, the internal mixing temperature is 160-180°C, the rotation speed is 40-50rpm, and then extruded and granulated, the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate further fill the Co-MOF composite graphene oxide catalytic carrier, the fixing effect of the carrier effectively reduces the migration and movement of organic components, the three act synergistically, increase the compatibility and dispersibility in epoxy resin, enhance the thermal stability of the flame retardant system, make the residual carbon layer after combustion present a continuous and more dense form, almost no gaps and holes appear, can better play the role of isolation and protection, effectively prevent the diffusion of smoke and heat, significantly improve the flame retardant properties, and obtain a phosphate composite flame retardant;

[0021] Preferably, in step S2, the amount of cobalt acetate tetrahydrate added is 40.0-50.0 mg, and the cobalt element can be used in combination with other flame retardant elements such as phosphorus, silicon, etc. to exert a synergistic flame retardant effect.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The present invention fills phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate on the Co-MOF composite graphene oxide catalytic carrier, effectively reducing the migration of components, enhancing the thermal stability of the flame retardant system, and also improving the compatibility and dispersibility in the epoxy resin matrix. The three act synergistically to make the residual carbon layer after combustion more dense and continuous, which can better play the role of isolation and protection, and significantly improve the flame retardant performance; in the phosphorus-nitrogen grafted coated network silica powder, firstly, the silica is modified by a network dispersing modifier to form The special network structure of silica particles connected to each other but with small gaps between the particles reduces the aggregation and migration of particles. Then polydopamine is coated on the silica particles to enhance the compatibility in epoxy resin, and is also conducive to the grafting of phosphorus and nitrogen elements on the surface of polydopamine@network silica. The phosphorus and nitrogen small molecules are degraded by heat, which effectively promotes the dehydration of the epoxy resin matrix into carbon, and synergizes with the protective layer formed when the polydopamine@network silica particles burns to block the release of heat and smoke, effectively enhancing the flame retardant performance. The Co-MOF composite oxidation In the graphene catalytic carrier, Co-MOF is evenly distributed on the surface of graphene oxide. The formed composite carrier has a compact and large surface area layer structure, which can better carry the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate, further enhance the thermal stability and reduce the migration of components, and also enhance the compatibility and dispersion effect in epoxy resin. At the same time, it also has the catalytic performance of promoting the carbonization reaction, so that each component can fully play the flame retardant effect, and under the filling effect of the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate, The carbon layer generated after combustion is denser and continuous, maintains a certain geometric shape, is not easy to fall off, and the coverage of the carbon layer is denser and wider, which can give full play to the isolation and protection effects, effectively prevent the diffusion of smoke and heat, and significantly improve the flame retardant performance; the present invention uses phosphorus-nitrogen grafted coated network silica powder, Co-MOF composite graphene oxide catalytic carrier and pentaerythritol phosphate to prepare a phosphate composite flame retardant, which effectively reduces the migration of components, enhances the thermal stability of the flame retardant system, and improves the compatibility in the epoxy resin matrix, thereby significantly improving the flame retardant performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the phosphorus-nitrogen grafted coated network silicon dioxide powder prepared in Example 1 of the present invention;

[0025] Figure 2 This is a cross-sectional scanning electron microscope image of the phosphate composite flame retardant and epoxy resin prepared in Example 1 of the present invention;

[0026] Figure 3 This is a scanning electron microscope image of the carbon residue after combustion of the phosphate composite flame retardant prepared in Example 1 of the present invention;

[0027] Figure 4 The limiting oxygen index results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0028] Figure 5 The peak heat release rate, total heat release and total smoke generation results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0029] Figure 6 This is a graph showing the ignition time results of Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0032] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0033] Example 1

[0034] This embodiment proposes a phosphate composite flame retardant, comprising the following components in parts by weight: 40 parts of phosphorus-nitrogen grafted coated network silica powder, 20 parts of Co-MOF composite graphene oxide catalytic carrier, and 20 parts of pentaerythritol phosphate.

[0035] The phosphorus-nitrogen grafted coated network silicon dioxide powder comprises the following components in parts by weight: 25 parts of a network dispersion modifier, 75 parts of silicon dioxide, 15 parts of dopamine hydrochloride, 6 parts of phosphorus oxychloride, and 8 parts of 4,4-diaminodiphenylmethane.

[0036] The Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 40 parts of Co-MOF and 15 parts of graphene oxide.

[0037] The method for preparing phosphorus-nitrogen grafted coated network silicon dioxide powder specifically comprises the following steps:

[0038] (1) 1 mol of KH550 and 1 mol of KH560 were added to a three-necked flask in a nitrogen atmosphere, heated to 130°C under magnetic stirring, stirred for 5 hours, and cooled to room temperature. The primary amine group of KH550 and the epoxy group of KH560 underwent an epoxy ring-opening reaction to synthesize a network-like substance with three alkoxy groups at both ends, thereby obtaining a network-like dispersing modifier;

[0039] (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, and then use hydrochloric acid solution to adjust the pH to 4.0. Then add the network dispersion modifier described in step (1). The amount of the network dispersion modifier added is 2.5 g. The alkoxy groups at both ends can react with the active hydroxyl groups on the surface of silica to achieve graft modification of silica. Stir at 50°C for 5 hours, and add 7.5 g of silica powder to the modified solution. At high temperature, silica can form a dense barrier layer on the surface of the material to isolate oxygen and heat. To prevent the spread of combustion, the temperature was raised to 60°C, the mixture was stirred for 5 hours, the stirring speed was 600 rpm, the mixture was dried, and the mixture was crushed. The alkoxy groups at both ends of the network-like dispersing modifier were simultaneously grafted onto different silica particles, connecting a large number of silica particles to form a network-like silica structure with a larger overall particle size. At the same time, there were certain gaps between the silica particles, which reduced the adsorption and aggregation between the particles and effectively increased the exchange interface of the flame retardant system, thereby improving the flame retardant properties of silica and obtaining a network-like silica.

[0040] (3) Weigh 1.0 g of the network silica described in step (2) and add it to 100 mL of Tris-HCl buffer and ultrasonically treat it for 20 min. Then, add dopamine hydrochloride to 200 mL of Tris-HCl buffer and dissolve it completely. Then, pour the network silica dispersion into it and ultrasonically treat it for 15 min. The amount of dopamine hydrochloride added is 1.5 g. Dopamine hydrochloride self-polymerizes to form a polydopamine protective layer, and the outer layer is evenly arranged with hydroxyl groups. Put it in a water bath environment at 25°C, stir it magnetically at a speed of 180 rpm for 12 h, and then centrifuge it twice. Centrifuge it for 20 min. The speed is 8000rpm, the first centrifugation time is 15min, the second centrifugation time is 10min, the precipitate is freeze-dried and ground, and polydopamine wraps the silica particles with a layer of "nano-coat" rich in catechol groups, which has excellent adhesion and film-forming properties and can be used for further modification and functionalization. It can improve its compatibility and dispersibility in the epoxy resin matrix and significantly improve its thermal stability. In addition, the polydopamine coating forms a protective layer during the combustion process, which can isolate oxygen and heat, thereby interrupting the combustion process and reducing the generation of smoke. Polydopamine@network silica is obtained;

[0041] (4) 1.0 g of the polydopamine@network-shaped silica described in step (3) was weighed, and 0.6 g of phosphorus oxychloride liquid, 50 mL of THF, and 0.3 g of triethylamine liquid were added to a 250 mL three-necked flask in sequence, and ultrasonicated at 25° C. for 1 h. Then, 0.8 g of 4,4-diaminodiphenylmethane solid was dissolved in 20 mL of THF and slowly dripped into the three-necked flask within 1 h. The mixture was allowed to react at room temperature for 24 h. The product was washed with THF and deionized water in sequence, and dried. Amine@network silica surface grafting introduces phosphorus and nitrogen elements, which improves the thermal stability and flame retardant properties of the composite. Polydopamine@network silica effectively adheres to the surface of epoxy resin and other substrates, isolating external combustible gases and heat from entering the interior of the substrate. Phosphorus and nitrogen small molecules will be the first to degrade when heated, effectively promoting the dehydration of the epoxy resin matrix into carbon, and synergistically acting with the protective layer formed when the silica particles burn to block the release of heat and smoke, thereby obtaining phosphorus-nitrogen grafted coated network silica powder.

[0042] This embodiment provides a method for preparing a phosphate composite flame retardant, which specifically includes the following steps:

[0043] S1. Add 70 mL of 98% concentrated sulfuric acid in an ice bath to a 1000 mL beaker, stir and add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 4 ° C, stir thoroughly, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 30 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after 15 min of reaction, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry. Graphene oxide can be used as a flame retardant additive. Its unique two-dimensional sheet structure can promote the material to form a dense and continuous carbon layer during the combustion process, isolate heat transfer and gas exchange with the outside world, and obtain graphene oxide;

[0044] S2. Add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water. The amount of cobalt acetate tetrahydrate added is 50.0 mg. Cobalt can be used in combination with other flame retardant elements such as phosphorus and silicon to exert a synergistic flame retardant effect. Stir for 1 hour, then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 170°C, and react for 72 hours. A new cobalt-based MOF material is synthesized by a hydrothermal method using a mixed ligand of cobalt salt and Fbtx and H2dcpa. The material has good thermal stability and adsorption, can maintain structural stability at high temperatures, and adsorb harmful gases and smoke produced by combustion, reducing the release of toxic gases in fires. The transition metal cobalt has catalytic properties and can promote carbonization reaction during combustion to form a more stable carbon layer, thereby isolating oxygen and heat and slowing down the combustion rate to obtain Co-MOF.

[0045] S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 200mL of methanol solution, ultrasonically dispersing for 50min, stirring for 2h, standing for precipitation, filtering and washing, and drying. The Co-MOF is evenly distributed on the surface of the graphene oxide and tightly combined. The carbon layer generated by the combustion of the formed composite carrier is dense and maintains a certain geometric shape, is not easy to fall off, and the coverage of the carbon layer is denser and wider. At the same time, in the composite carrier, the graphene oxide can also promote the rapid carbonization of the polymer and produce a variety of non-combustible gases when thermally decomposed. These gases can isolate oxygen from contact with combustible gases and block the continuous combustion conditions, thereby playing a flame retardant role, and obtaining a Co-MOF composite graphene oxide catalytic carrier;

[0046] S4, the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3 and pentaerythritol phosphate are uniformly mixed. The molecular structure of pentaerythritol phosphate presents a highly symmetrical cage shape, has excellent thermal stability and carbon-forming property, and provides abundant acid source and carbon source. The mixture is melt-blended in an internal mixer at a mixing temperature of 180° C. and a rotation speed of 50 rpm. The mixture is then extruded and granulated. The phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate further fill the Co-MOF composite graphene oxide catalytic carrier. The fixing effect of the carrier effectively reduces the migration and movement of organic components. The three act synergistically to increase the compatibility and dispersibility in the epoxy resin, enhance the thermal stability of the flame retardant system, and make the residual carbon layers after combustion present a continuous and denser form, with almost no gaps and holes, so that the isolation and protection effects can be better exerted, the diffusion of smoke and heat can be effectively prevented, the flame retardant properties are significantly improved, and the phosphate composite flame retardant is obtained.

[0047] In this embodiment, the prepared phosphorus-nitrogen grafted coated network silicon dioxide powder, the cross section of the phosphate composite flame retardant and the epoxy resin, and the carbon residue after combustion of the phosphate composite flame retardant were subjected to scanning electron microscopy to observe their microscopic morphology. Figure 1 This is a SEM image of the phosphorus-nitrogen grafted and coated network-like silica powder prepared in Example 1, magnified 100,000 times. Figure 2 This is a SEM image of the cross section of the phosphate composite flame retardant and epoxy resin prepared in Example 1, magnified 500 times. Figure 3 This is a SEM image of the carbon residue after combustion of the phosphate composite flame retardant prepared in Example 1, magnified 200 times. Figure 1 The phosphorus-nitrogen grafted coated network silica powder prepared in this embodiment presents a network structure in which rough silica particles are connected but have gaps, such as Figure 2 The phosphate composite flame retardant prepared in this embodiment has good cross-sectional compatibility and dispersibility with epoxy resin, such as Figure 3The char residue after combustion of the phosphate composite flame retardant prepared in this embodiment presents a continuous and dense structure.

[0048] Example 2

[0049] This embodiment proposes a phosphate composite flame retardant, comprising the following components in parts by weight: 30 parts of phosphorus-nitrogen grafted coated network silica powder, 10 parts of Co-MOF composite graphene oxide catalytic carrier, and 10 parts of pentaerythritol phosphate.

[0050] The phosphorus-nitrogen grafted coated network silicon dioxide powder comprises the following components in parts by weight: 20 parts of a network dispersion modifier, 60 parts of silicon dioxide, 10 parts of dopamine hydrochloride, 3 parts of phosphorus oxychloride, and 6 parts of 4,4-diaminodiphenylmethane.

[0051] The Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 30 parts of Co-MOF and 10 parts of graphene oxide.

[0052] The method for preparing phosphorus-nitrogen grafted coated network silicon dioxide powder specifically comprises the following steps:

[0053] (1) 1 mol of KH550 and 1 mol of KH560 were added to a three-necked flask in a nitrogen atmosphere, heated to 120°C under magnetic stirring, stirred for 3 hours, and cooled to room temperature. The primary amine group of KH550 and the epoxy group of KH560 underwent an epoxy ring-opening reaction to synthesize a network-like substance with three alkoxy groups at both ends, thereby obtaining a network-like dispersing modifier;

[0054] (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, and then use hydrochloric acid solution to adjust the pH to 4.0. Then add the network dispersion modifier described in step (1). The amount of the network dispersion modifier added is 2.0 g. The alkoxy groups at both ends can react with the active hydroxyl groups on the surface of silica to achieve graft modification of silica. Stir at 40°C for 4 hours, and add 6.0 g of silica powder to the modified solution. At high temperature, silica can form a dense barrier layer on the surface of the material to isolate oxygen and heat. To prevent the spread of combustion, the temperature was raised to 60°C, the mixture was stirred for 4 hours at a stirring speed of 500 rpm, and the mixture was dried and crushed. The alkoxy groups at both ends of the network-like dispersing modifier were simultaneously grafted onto different silica particles, connecting a large number of silica particles to form a network-like silica structure with a larger overall particle size. At the same time, there were certain gaps between the silica particles, which reduced the adsorption and aggregation between the particles and effectively increased the exchange interface of the flame retardant system, thereby improving the flame retardant properties of silica and obtaining a network-like silica.

[0055] (3) Weigh 0.6 g of the network silica described in step (2) and add it to 100 mL of Tris-HCl buffer and ultrasonically treat it for 10 min. Then, add dopamine hydrochloride to 200 mL of Tris-HCl buffer and dissolve it completely. Then, pour the network silica dispersion into it and ultrasonically treat it for 10 min. The amount of dopamine hydrochloride added is 1.0 g. Dopamine hydrochloride self-polymerizes to form a polydopamine protective layer, and the outer layer is evenly arranged with hydroxyl groups. Put it in a water bath environment at 25°C, stir it magnetically at a speed of 160 rpm for 6 hours, and then centrifuge it twice. Centrifuge it for 2 minutes. The speed is 7000rpm, the first centrifugation time is 15min, the second centrifugation time is 10min, the precipitate is freeze-dried and ground, and polydopamine wraps the silica particles with a layer of "nano-coat" rich in catechol groups, which has excellent adhesion and film-forming properties and can be used for further modification and functionalization. It can improve its compatibility and dispersibility in the epoxy resin matrix and significantly improve its thermal stability. In addition, the polydopamine coating forms a protective layer during the combustion process, which can isolate oxygen and heat, thereby interrupting the combustion process and reducing the generation of smoke. Polydopamine@network silica is obtained;

[0056] (4) Weigh 0.5 g of the polydopamine@network-shaped silica described in step (3), 0.3 g of phosphorus oxychloride liquid, 50 mL of THF and 0.3 g of triethylamine liquid, add them into a 250 mL three-necked flask in sequence, and ultrasonicate at 25°C for 0.5 h. Then, 0.6 g of 4,4-diaminodiphenylmethane solid is dissolved in 20 mL of THF and slowly dripped into the three-necked flask within 1 h. The mixture is allowed to react at room temperature for 24 h. The product is washed with THF and deionized water in sequence, dried, and The surface of polydopamine@network-like silica is grafted with phosphorus and nitrogen elements, which improves the thermal stability and flame retardancy of the composite. Polydopamine@network-like silica effectively adheres to the surface of epoxy resin and other substrates, isolating external combustible gases and heat from entering the interior of the substrate. Phosphorus and nitrogen small molecules will be degraded first when heated, effectively promoting the dehydration of the epoxy resin matrix into carbon, and synergizing with the protective layer formed when the silica particles burn to block the release of heat and smoke, thus obtaining phosphorus-nitrogen grafted coated network-like silica powder.

[0057] This embodiment provides a method for preparing a phosphate composite flame retardant, which specifically includes the following steps:

[0058] S1. Add 70 mL of 98% concentrated sulfuric acid to a 1000 mL beaker under an ice bath, stir and add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 0 ° C, stir thoroughly, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 10 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after 15 min of reaction, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry. Graphene oxide can be used as a flame retardant additive. Its unique two-dimensional sheet structure can promote the material to form a dense and continuous carbon layer during the combustion process, isolate heat transfer and gas exchange with the outside world, and obtain graphene oxide;

[0059] S2. Add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water. The amount of cobalt acetate tetrahydrate added is 40.0 mg. Cobalt can be used in combination with other flame retardant elements such as phosphorus and silicon to exert a synergistic flame retardant effect. Stir for 0.5 h, then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 160 ° C, and react for 48 h. A new cobalt-based MOF material is synthesized by a hydrothermal method using a mixed ligand of cobalt salt and Fbtx and H2dcpa. It has good thermal stability and adsorption, can maintain structural stability at high temperatures, and adsorb harmful gases and smoke produced by combustion, reducing the release of toxic gases in fires. The transition metal cobalt has catalytic properties and can promote carbonization reaction during combustion to form a more stable carbon layer, thereby isolating oxygen and heat, slowing down the combustion rate, and obtaining Co-MOF.

[0060] S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 100mL of methanol solution, ultrasonically dispersing for 30min, stirring for 1h, standing for precipitation, filtering and washing, and drying. The Co-MOF is evenly distributed on the surface of the graphene oxide and tightly combined. The carbon layer generated by the combustion of the formed composite carrier is dense and maintains a certain geometric shape, is not easy to fall off, and the coverage of the carbon layer is denser and wider. At the same time, in the composite carrier, the graphene oxide can also promote the rapid carbonization of the polymer and produce a variety of non-combustible gases when thermally decomposed. These gases can isolate oxygen from contact with combustible gases and block the continuous combustion conditions, thereby playing a flame retardant role, and obtaining a Co-MOF composite graphene oxide catalytic carrier;

[0061] S4, the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3 and pentaerythritol phosphate are uniformly mixed. The molecular structure of pentaerythritol phosphate presents a highly symmetrical cage shape, has excellent thermal stability and carbon-forming property, and provides abundant acid source and carbon source. The mixture is melt-blended in an internal mixer at a mixing temperature of 160° C. and a rotation speed of 40 rpm. The mixture is then extruded and granulated. The phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate further fill the Co-MOF composite graphene oxide catalytic carrier. The fixing effect of the carrier effectively reduces the migration and movement of organic components. The three act synergistically to increase the compatibility and dispersibility in the epoxy resin, enhance the thermal stability of the flame retardant system, and make the residual carbon layers after combustion present a continuous and denser form, with almost no gaps and holes, so that the isolation and protection effects can be better exerted, the diffusion of smoke and heat can be effectively prevented, the flame retardant properties are significantly improved, and the phosphate composite flame retardant is obtained.

[0062] Example 3

[0063] This embodiment proposes a phosphate composite flame retardant, comprising the following components in parts by weight: 35 parts of phosphorus-nitrogen grafted coated network silica powder, 15 parts of Co-MOF composite graphene oxide catalytic carrier, and 15 parts of pentaerythritol phosphate.

[0064] The phosphorus-nitrogen grafted coated network silicon dioxide powder comprises the following components in parts by weight: 22.5 parts of a network dispersing modifier, 67.5 parts of silicon dioxide, 12.5 parts of dopamine hydrochloride, 4.5 parts of phosphorus oxychloride, and 7 parts of 4,4-diaminodiphenylmethane.

[0065] The Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 35 parts of Co-MOF and 12.5 parts of graphene oxide.

[0066] The method for preparing phosphorus-nitrogen grafted coated network silicon dioxide powder specifically comprises the following steps:

[0067] (1) 1 mol of KH550 and 1 mol of KH560 were added to a three-necked flask in a nitrogen atmosphere, heated to 125°C under magnetic stirring, stirred for 4 hours, and cooled to room temperature. The primary amine group of KH550 and the epoxy group of KH560 underwent an epoxy ring-opening reaction to synthesize a network-like substance with three alkoxy groups at both ends, thereby obtaining a network-like dispersing modifier;

[0068] (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, and then use hydrochloric acid solution to adjust the pH to 4.0. Then add the network dispersion modifier described in step (1). The amount of the network dispersion modifier added is 2.25 g. The alkoxy groups at both ends can react with the active hydroxyl groups on the surface of silica to achieve graft modification of silica. Stir at 45°C for 4.5 hours, and add 6.75 g of silica powder to the modified solution. At high temperature, silica can form a dense barrier layer on the surface of the material to isolate oxygen and heat. , prevent the spread of combustion, heat to 60°C, stir and mix thoroughly for 4.5h, stir at 550rpm, dry, crush, and graft the alkoxy groups at both ends of the network dispersing modifier onto different silica particles at the same time, connecting a large number of silica particles to form a network silica structure with a larger overall particle size. At the same time, there are certain gaps between the silica particles, which reduces the adsorption and aggregation between the particles and effectively increases the exchange interface of the flame retardant system, thereby improving the flame retardant properties of silica and obtaining network silica;

[0069] (3) Weigh 0.8 g of the network silica described in step (2) and add it to 100 mL of Tris-HCl buffer and ultrasonically treat it for 15 min. Then, add dopamine hydrochloride to 200 mL of Tris-HCl buffer and dissolve it completely. Then, pour the network silica dispersion into it and ultrasonically treat it for 12.5 min. The amount of dopamine hydrochloride added is 1.25 g. Dopamine hydrochloride self-polymerizes to form a polydopamine protective layer, and the outer layer is evenly arranged with hydroxyl groups. Put it in a water bath environment at 25°C, stir it magnetically at a speed of 170 rpm for 9 hours, and then centrifuge it twice. The rotation speed is 7500rpm, the first centrifugation time is 15min, the second centrifugation time is 10min, the precipitate is freeze-dried and ground, and polydopamine wraps the silica particles with a layer of "nano-coat" rich in catechol groups, which has excellent adhesion and film-forming properties and can be used for further modification and functionalization. It can improve its compatibility and dispersibility in the epoxy resin matrix and significantly improve thermal stability. In addition, the polydopamine coating forms a protective layer during the combustion process, which can isolate oxygen and heat, thereby interrupting the combustion process and reducing the generation of smoke. Polydopamine@network silica is obtained;

[0070] (4) 0.75 g of the polydopamine@network-shaped silica described in step (3) was weighed, and 0.45 g of phosphorus oxychloride liquid, 50 mL of THF and 0.3 g of triethylamine liquid were added to a 250 mL three-necked flask in sequence, and ultrasonicated at 25°C for 0.75 h. Then 0.7 g of 4,4-diaminodiphenylmethane solid was dissolved in 20 mL of THF and slowly dripped into the three-necked flask within 1 h. The mixture was allowed to react at room temperature for 24 h. The product was washed with THF and deionized water in sequence, and dried. Dopamine@network silica surface grafting introduces phosphorus and nitrogen elements, which improves the thermal stability and flame retardant properties of the composite. Polydopamine@network silica effectively adheres to the surface of epoxy resin and other substrates, isolating external combustible gases and heat from entering the interior of the substrate. Phosphorus and nitrogen small molecules will be the first to degrade when heated, effectively promoting the dehydration of the epoxy resin matrix into carbon, and synergistically acting with the protective layer formed when the silica particles burn to block the release of heat and smoke, thereby obtaining phosphorus-nitrogen grafted coated network silica powder.

[0071] This embodiment provides a method for preparing a phosphate composite flame retardant, which specifically includes the following steps:

[0072] S1. Add 70 mL of 98% concentrated sulfuric acid in an ice bath to a 1000 mL beaker, stir and add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 2 ° C, stir thoroughly, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 20 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after 15 min of reaction, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry. Graphene oxide can be used as a flame retardant additive. Its unique two-dimensional sheet structure can promote the material to form a dense and continuous carbon layer during the combustion process, isolate heat transfer and gas exchange with the outside world, and obtain graphene oxide;

[0073] S2. Add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water. The amount of cobalt acetate tetrahydrate added is 45.0 mg. Cobalt can be used in combination with other flame retardant elements such as phosphorus and silicon to exert a synergistic flame retardant effect. Stir for 0.75 h, then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 165 ° C, and react for 60 h. A new cobalt-based MOF material is synthesized by a hydrothermal method using a mixed ligand of cobalt salt and Fbtx and H2dcpa. It has good thermal stability and adsorption, can maintain structural stability at high temperatures, and adsorb harmful gases and smoke produced by combustion, reducing the release of toxic gases in fires. The transition metal cobalt has catalytic properties and can promote carbonization reaction during combustion to form a more stable carbon layer, thereby isolating oxygen and heat, slowing down the combustion rate, and obtaining Co-MOF.

[0074] S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 150mL of methanol solution, ultrasonically dispersing for 40min, stirring for 1.5h, standing to precipitate, filtering and washing, and drying. The Co-MOF is evenly distributed on the surface of the graphene oxide and tightly combined. The carbon layer generated by the combustion of the formed composite carrier is dense and maintains a certain geometric shape, is not easy to fall off, and the carbon layer covers a denser and wider degree. At the same time, in the composite carrier, the graphene oxide can also promote the rapid carbonization of the polymer and produce a variety of non-combustible gases when thermally decomposed. These gases can isolate oxygen from contact with combustible gases and block the continuous combustion conditions, thereby playing a flame retardant role, and obtaining a Co-MOF composite graphene oxide catalytic carrier;

[0075] S4, the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3 and pentaerythritol phosphate are uniformly mixed, the molecular structure of pentaerythritol phosphate presents a highly symmetrical cage shape, has excellent thermal stability and carbon-forming property, and provides abundant acid source and carbon source at the same time, the mixture is melt-blended in an internal mixer, the internal mixing temperature is 170° C., the rotation speed is 45 rpm, and then extruded and granulated, the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate further fill the Co-MOF composite graphene oxide catalytic carrier, the fixing effect of the carrier effectively reduces the migration and movement of organic components, the three act synergistically, increase the compatibility and dispersibility in epoxy resin, enhance the thermal stability of the flame retardant system, make the residual carbon layer after combustion present a continuous and denser form, almost no gaps and holes appear, can better play the role of isolation and protection, effectively prevent the diffusion of smoke and heat, significantly improve the flame retardant properties, and obtain a phosphate composite flame retardant.

[0076] Example 4

[0077] This embodiment proposes a phosphate composite flame retardant, comprising the following components in parts by weight: 30 parts of phosphorus-nitrogen grafted coated network silica powder, 10 parts of Co-MOF composite graphene oxide catalytic carrier, and 20 parts of pentaerythritol phosphate.

[0078] The phosphorus-nitrogen grafted coated network silicon dioxide powder comprises the following components in parts by weight: 20 parts of a network dispersion modifier, 75 parts of silicon dioxide, 15 parts of dopamine hydrochloride, 3 parts of phosphorus oxychloride, and 6 parts of 4,4-diaminodiphenylmethane.

[0079] The Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 30 parts of Co-MOF and 15 parts of graphene oxide.

[0080] The method for preparing phosphorus-nitrogen grafted coated network silicon dioxide powder specifically comprises the following steps:

[0081] (1) 1 mol of KH550 and 1 mol of KH560 were added to a three-necked flask in a nitrogen atmosphere, heated to 130°C under magnetic stirring, stirred for 3 hours, and cooled to room temperature. The primary amine group of KH550 and the epoxy group of KH560 underwent an epoxy ring-opening reaction to synthesize a network-like substance with three alkoxy groups at both ends, thereby obtaining a network-like dispersing modifier;

[0082] (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, and then use hydrochloric acid solution to adjust the pH to 4.0. Then add the network dispersion modifier described in step (1). The amount of the network dispersion modifier added is 2.0 g. The alkoxy groups at both ends can react with the active hydroxyl groups on the surface of silica to achieve graft modification of silica. Stir at 50°C for 4 hours, and add 7.5 g of silica powder to the modified solution. At high temperature, silica can form a dense barrier layer on the surface of the material to isolate oxygen and heat. To prevent the spread of combustion, the temperature was raised to 60°C, the mixture was stirred for 4 hours at a stirring speed of 600 rpm, dried, crushed, and the alkoxy groups at both ends of the network-like dispersing modifier were simultaneously grafted onto different silica particles, connecting a large number of silica particles to form a network-like silica structure with a larger overall particle size. At the same time, there were certain gaps between the silica particles, which reduced the adsorption and aggregation between the particles and effectively increased the exchange interface of the flame retardant system, thereby improving the flame retardant properties of silica and obtaining a network-like silica.

[0083] (3) 1.0 g of the network silica described in step (2) was weighed and added to 100 mL of Tris-HCl buffer and ultrasonically treated for 10 min. Dopamine hydrochloride was then added to 200 mL of Tris-HCl buffer and dissolved completely. The network silica dispersion was then poured into the dispersion and ultrasonically treated for 10 min. The amount of dopamine hydrochloride added was 1.5 g. Dopamine hydrochloride self-polymerized to form a polydopamine protective layer with evenly distributed hydroxyl groups arranged on the outer layer. The dispersion was placed in a water bath at 25°C and magnetically stirred at 180 rpm for 6 h. The dispersion was then centrifuged twice. The speed is 8000rpm, the first centrifugation time is 15min, the second centrifugation time is 10min, the precipitate is freeze-dried and ground, and polydopamine wraps the silica particles with a layer of "nano-coat" rich in catechol groups, which has excellent adhesion and film-forming properties and can be used for further modification and functionalization. It can improve its compatibility and dispersibility in the epoxy resin matrix and significantly improve its thermal stability. In addition, the polydopamine coating forms a protective layer during the combustion process, which can isolate oxygen and heat, thereby interrupting the combustion process and reducing the generation of smoke. Polydopamine@network silica is obtained;

[0084] (4) 1.0 g of the polydopamine@network-shaped silica described in step (3) was weighed, and 0.3 g of phosphorus oxychloride liquid, 50 mL of THF and 0.3 g of triethylamine liquid were added to a 250 mL three-necked flask in sequence, and ultrasonicated at 25°C for 0.5 h. Then 0.6 g of 4,4-diaminodiphenylmethane solid was dissolved in 20 mL of THF and slowly dripped into the three-necked flask within 1 h. The mixture was allowed to react at room temperature for 24 h. The product was washed with THF and deionized water in sequence, and dried. The surface of polydopamine@network-like silica is grafted with phosphorus and nitrogen elements, which improves the thermal stability and flame retardancy of the composite. Polydopamine@network-like silica effectively adheres to the surface of epoxy resin and other substrates, isolating external combustible gases and heat from entering the interior of the substrate. Phosphorus and nitrogen small molecules will be degraded first when heated, effectively promoting the dehydration of the epoxy resin matrix into carbon, and synergizing with the protective layer formed when the silica particles burn to block the release of heat and smoke, thus obtaining phosphorus-nitrogen grafted coated network-like silica powder.

[0085] This embodiment provides a method for preparing a phosphate composite flame retardant, which specifically includes the following steps:

[0086] S1. Add 70 mL of 98% concentrated sulfuric acid to a 1000 mL beaker under an ice bath, stir and add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 4 ° C, stir thoroughly, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 10 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after 15 min of reaction, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry. Graphene oxide can be used as a flame retardant additive. Its unique two-dimensional sheet structure can promote the material to form a dense and continuous carbon layer during the combustion process, isolate heat transfer and gas exchange with the outside world, and obtain graphene oxide;

[0087] S2. Add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water. The amount of cobalt acetate tetrahydrate added is 40.0 mg. Cobalt can be used in combination with other flame retardant elements such as phosphorus and silicon to exert a synergistic flame retardant effect. Stir for 0.5 h, then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 170 ° C, and react for 48 h. A new cobalt-based MOF material is synthesized by a hydrothermal method using a mixed ligand of cobalt salt and Fbtx and H2dcpa. It has good thermal stability and adsorption, can maintain structural stability at high temperatures, and adsorb harmful gases and smoke produced by combustion, reducing the release of toxic gases in fires. The transition metal cobalt has catalytic properties and can promote carbonization reaction during combustion to form a more stable carbon layer, thereby isolating oxygen and heat, slowing down the combustion rate, and obtaining Co-MOF.

[0088] S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 200mL of methanol solution, ultrasonically dispersing for 30min, stirring for 1h, standing for precipitation, filtering and washing, and drying. The Co-MOF is evenly distributed on the surface of the graphene oxide and tightly combined. The carbon layer generated by the combustion of the formed composite carrier is dense and maintains a certain geometric shape, is not easy to fall off, and the coverage of the carbon layer is denser and wider. At the same time, in the composite carrier, the graphene oxide can also promote the rapid carbonization of the polymer and produce a variety of non-combustible gases when thermally decomposed. These gases can isolate oxygen from contact with combustible gases and block the continuous combustion conditions, thereby playing a flame retardant role, and obtaining a Co-MOF composite graphene oxide catalytic carrier;

[0089] S4, the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3 and pentaerythritol phosphate are uniformly mixed. The molecular structure of pentaerythritol phosphate presents a highly symmetrical cage shape, has excellent thermal stability and carbon-forming property, and provides abundant acid source and carbon source. The mixture is melt-blended in an internal mixer at a mixing temperature of 180° C. and a rotation speed of 50 rpm. The mixture is then extruded and granulated. The phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate further fill the Co-MOF composite graphene oxide catalytic carrier. The fixing effect of the carrier effectively reduces the migration and movement of organic components. The three act synergistically to increase the compatibility and dispersibility in the epoxy resin, enhance the thermal stability of the flame retardant system, and make the residual carbon layers after combustion present a continuous and denser form, with almost no gaps and holes, so that the isolation and protection effects can be better exerted, the diffusion of smoke and heat can be effectively prevented, the flame retardant properties are significantly improved, and the phosphate composite flame retardant is obtained.

[0090] Comparative Example 1

[0091] This comparative example provides a phosphate composite flame retardant, which is different from Example 1 in that the phosphorus-nitrogen grafted coated network silica powder does not contain a network dispersing modifier; the preparation method of the phosphorus-nitrogen grafted coated network silica powder does not include step (1); and the preparation method of the phosphate composite flame retardant is the same as that of Example 1.

[0092] Comparative Example 2

[0093] This comparative example provides a phosphate composite flame retardant, which differs from Example 1 in that the phosphorus-nitrogen grafted coated network silica powder does not contain dopamine hydrochloride; the preparation method of the phosphorus-nitrogen grafted coated network silica powder does not include step (3); and the preparation method of the phosphate composite flame retardant is the same as that of Example 1.

[0094] Comparative Example 3

[0095] This comparative example provides a phosphate composite flame retardant, which differs from Example 1 in that the Co-MOF composite graphene oxide catalytic carrier does not contain Co-MOF; the preparation method of the phosphorus-nitrogen grafted coated network silica powder is the same as that of Example 1; and the preparation method of the phosphate composite flame retardant does not include step S2.

[0096] Experimental Example 1

[0097] Flame retardant performance test

[0098] Test sample: the phosphate composite flame retardant prepared in Examples 1-4 and Comparative Examples 1-3.

[0099] Test method: The test sample is added in a ratio of 15% and the epoxy resin is cured by high temperature to prepare the sample. Then the sample is tested as follows: Limiting oxygen index test (LOI) is tested in accordance with GB / T2406-2009, and the sample size is 100mm×6.5mm×3mm; cone calorimetry test is tested in accordance with ISO5660-1 to obtain the peak heat release rate (kW / m 2 )、Total heat release(MJ / m 2 )、Total smoke generation(m 2 / m 2 ) and ignition time (s), where the thermal radiation flux during the test is 50kW / m 2 , the sample size is 100mm×100mm×3mm.

[0100] Figure 4 The limiting oxygen index results of Examples 1-4 and Comparative Examples 1-3 are shown in FIG. Figure 5 The results of the peak heat release rate, total heat release and total smoke generation of Examples 1-4 and Comparative Examples 1-3 are shown in FIG. Figure 6 Result diagram of ignition time of Examples 1-4 and Comparative Examples 1-3; Figure 4 , the limiting oxygen index of Examples 1-4 is 34.0-35.8%, such as Figure 5 The peak heat release rate, total heat release and total smoke generation of Examples 1-4 are 153-186 kW / m 2 、46-56MJ / m 2 、165-182m 2 / m 2 ,like Figure 6 , the ignition time of Examples 1-4 is 112-120s, the limiting oxygen index is high, the peak heat release rate, the total heat release and the total smoke generation are low, and the ignition time is long, indicating that the flame retardant performance is good; Figure 4 , the limiting oxygen index of comparative examples 1-3 is 22.3-30.8%, such as Figure 5 The peak heat release rate, total heat release and total smoke generation of comparative examples 1-3 were 227-298 kW / m 2 、69-87MJ / m 2 、209-246m 2 / m 2 ,like Figure 6The ignition time of comparative examples 1-3 is 89-102s, indicating that the flame retardant performance is average; the phosphorus-nitrogen grafted coated network silica powder of comparative example 1 does not contain a network dispersing modifier, and cannot form a network structure between particles, which increases the aggregation and migration of silica, which is not conducive to the isolation and protection of the protective layer, resulting in average flame retardant performance; the phosphorus-nitrogen grafted coated network silica powder of comparative example 2 does not contain dopamine hydrochloride, and cannot coat the silica particles to enhance the compatibility in the epoxy resin, nor is it conducive to the grafting of phosphorus and nitrogen elements on the particle surface to play a role Synergistic flame retardant effect, thus unable to effectively block oxygen, heat and smoke, resulting in general flame retardant performance; the Co-MOF composite graphene oxide catalytic carrier of Comparative Example 3 does not contain Co-MOF, which is not conducive to reducing the agglomeration of graphene oxide, and cannot form a tighter and larger surface area sheet structure, and cannot better carry the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate, which is not conducive to the dense continuity and coverage of the combustion carbon layer, and cannot give full play to the isolation and protection, and cannot play the catalytic performance of promoting the carbonization reaction, resulting in general flame retardant performance.

[0101] The above experimental results show that the flame retardant properties of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, the flame retardant properties of Example 1 using phosphorus-nitrogen grafted coated network silica powder and Co-MOF composite graphene oxide catalytic carrier are better. In the phosphorus-nitrogen grafted coated network silica powder, the silica is first modified by a network dispersing modifier to form a special network structure in which the silica particles are interconnected but there are small gaps between the particles, which reduces the aggregation and migration of the particles. Then, polydopamine is coated on the silica particles to enhance the compatibility in the epoxy resin, and is also conducive to the grafting of phosphorus and nitrogen elements on the surface of the polydopamine@network silica, which effectively enhances the flame retardant properties. Co-MOF is evenly distributed on the The composite carrier formed on the surface of graphene oxide has a compact and large surface area lamellar structure, which can better carry the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate, further enhance the thermal stability and reduce the migration of components, and also enhance the compatibility and dispersibility in epoxy resin. At the same time, it also has catalytic performance to promote carbonization reaction, so that each component can fully play the flame retardant effect, and under the filling effect of the phosphorus-nitrogen grafted coated network silica powder and pentaerythritol phosphate, the carbon layer generated after combustion is more dense and continuous, and maintains a certain geometric shape and is not easy to fall off. In addition, the coverage of the carbon layer is denser and wider, which can give full play to the isolation and protection role, effectively prevent the diffusion of smoke and heat, and significantly improve the flame retardant performance.

[0102] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0103] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A phosphate composite flame retardant, characterized in that: The phosphate composite flame retardant comprises the following components in parts by weight: 30-40 parts of phosphorus-nitrogen grafted coated networked silica powder, 10-20 parts of Co-MOF composite graphene oxide catalytic carrier, and 10-20 parts of pentaerythritol phosphate; the phosphorus-nitrogen grafted coated networked silica powder comprises the following components in parts by weight: 20-25 parts of a networked dispersing modifier, 60-75 parts of silicon dioxide, 10-15 parts of dopamine hydrochloride, 3-6 parts of phosphorus oxychloride, and 6-8 parts of 4,4-diaminodiphenylmethane; the Co-MOF composite graphene oxide catalytic carrier comprises the following components in parts by weight: 30-40 parts of Co-MOF and 10-15 parts of graphene oxide.

2. A method for preparing the phosphate composite flame retardant according to claim 1, characterized in that: The specific steps include: S1. Add 70 mL of 98% concentrated sulfuric acid in an ice bath to a 1000 mL beaker, stir, add 3.0 g of graphite powder and 1.5 g of sodium nitrate, control the temperature to 0-4 ° C, stir well, slowly add 9.0 g of potassium permanganate, then heat to 40 ° C, react for 10-30 min, then slowly add the above solution to 140 mL of deionized water, quickly heat to 98 ° C, stop heating after reacting for 15 min, cool, then add 15 mL of hydrogen peroxide solution and 420 mL of deionized water, filter, centrifuge, wash, and dry to obtain graphene oxide; S2, add cobalt acetate tetrahydrate powder, 94.0 mg Fbtx, and 60.0 mg H2dcpa to 7 mL deionized water, stir for 0.5-1 h, and then transfer to a reactor lined with polytetrafluoroethylene, control the temperature at 160-170 ° C, and react for 48-72 h to obtain Co-MOF; S3, pouring the graphene oxide described in step S1 and the Co-MOF described in step S2 into 100-200 mL of methanol solution, ultrasonically dispersing for 30-50 min, stirring for 1-2 h, standing for precipitation, filtering and washing, and drying to obtain a Co-MOF composite graphene oxide catalytic carrier; S4, uniformly mix the phosphorus-nitrogen grafted coated network silica powder, the Co-MOF composite graphene oxide catalytic carrier described in step S3, and pentaerythritol phosphate, melt blend them in an internal mixer at a mixing temperature of 160-180° C. and a rotation speed of 40-50 rpm, and then extrude and granulate to obtain a phosphate composite flame retardant.

3. The method for preparing the phosphate composite flame retardant according to claim 2, characterized in that: In step S2, the amount of cobalt acetate tetrahydrate added is 40.0-50.0 mg.

4. The method for preparing the phosphate composite flame retardant according to claim 3, characterized in that: The method for preparing the phosphorus-nitrogen grafted coated network-shaped silica powder specifically comprises the following steps: (1) Add 1 mol of KH550 and 1 mol of KH560 into a three-necked flask in a nitrogen atmosphere, heat to 120-130°C under magnetic stirring, stir for 3-5 hours, and cool to room temperature to obtain a network-like dispersion modifier; (2) Add 90 mL of anhydrous ethanol and 10 mL of water into a beaker, adjust the pH to 4.0 with hydrochloric acid solution, then add the network dispersion modifier described in step (1), stir at 40-50° C. for 4-5 hours, add 6.0-7.5 g of silicon dioxide powder to the modified solution, heat to 60° C., stir and mix thoroughly for 4-5 hours at a stirring speed of 500-600 rpm, dry, and crush to obtain network silicon dioxide; (3) Weigh 0.6-1.0 g of the network silica described in step (2) and add it to 100 mL of Tris-HCl buffer, and ultrasonically treat it for 10-20 min. Then, add dopamine hydrochloride to 200 mL of Tris-HCl buffer to completely dissolve it. Then, pour the network silica dispersion into it, and ultrasonically treat it for 10-15 min. Put it in a 25°C water bath environment, and magnetically stir it at a speed of 160-180 rpm for 6-12 h. Then, centrifuge it twice at a centrifugal speed of 7000-8000 rpm, the first centrifugation time is 15 min, and the second centrifugation time is 10 min. The precipitate is freeze-dried and ground to obtain polydopamine@network silica; (4) Weigh 0.5-1.0 g of the polydopamine@network silica described in step (3), 0.3-0.6 g of phosphorus oxychloride liquid, 50 mL of THF and 0.3 g of triethylamine liquid, add them into a 250 mL three-necked flask in sequence, and ultrasonicate at 25° C. for 0.5-1 h. Then, dissolve 0.6-0.8 g of 4,4-diaminodiphenylmethane solid in 20 mL of THF and slowly drip it into the three-necked flask within 1 h. Let it react at room temperature for 24 h. The product is washed with THF and deionized water in sequence and dried to obtain phosphorus-nitrogen grafted coated network silica powder.

5. The method for preparing the phosphate composite flame retardant according to claim 4, characterized in that: In step (2), the amount of network dispersion modifier added is 2.0-2.5 g.

6. The method for preparing the phosphate composite flame retardant according to claim 5, characterized in that: In step (3), the amount of dopamine hydrochloride added is 1.0-1.5 g.

Citation Information

Patent Citations

  • Preparation method and application of polyphosphate grafted graphene flame-retardant modified polypropylene

    CN114213759A

  • Co-MOF-74 composite material coated with graphene shell as well as preparation method and application of Co-MOF-74 composite material

    CN114682302A

  • Metal organic framework-graphene oxide composite adsorbent as well as preparation method and application thereof

    CN118384861A

  • Vitrification agent and preparation method thereof

    CN119040865A

  • Methods and apparatus for measuring fastener concentricity

    KR1020220099098A

Cited By

  • Concentrated grafted PVC efficient flame-retardant master batch material and preparation method thereof

    CN120040893A

  • Lightweight high-strength expandable polystyrene material and preparation method thereof

    CN121554887A

  • Anti-aging expandable polystyrene particles and preparation process thereof

    CN121975243A